2021
DOI: 10.1088/1361-648x/abce41
|View full text |Cite
|
Sign up to set email alerts
|

Subsurface depth dependence of nitrogen doping in TiO2 anatase: a DFT study

Abstract: We report first-principles calculations of the structure and electronic structure of nitrogen-doped TiO2 anatase as a function of the dopant depth below the (101) surface. Specifically we evaluate the depth dependence of the formation energy for a few positions of the N impurity, considering for both substitutional and interstitial sites. We find a significant advantage of interstitial over substitutional positions, and a mild dependence of this formation energy on depth. The lengths of the bonds surrounding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…The formation energy labeled as E f is defined as E normalf , N s = E normalN @ Ti 84 O 167 + 1 2 E normalO 2 1 2 E normalN 2 E Ti 84 O 168 E normalf , N i = E normalN @ Ti 84 O 168 1 2 E normalN 2 E Ti 84 O 168 where E N@Ti 84 O 167 and E N@Ti 84 O 168 correspond to the total energies of substitutional and interstitial doped NPs, respectively; E Ti 84 O 168 is the total energy of the undoped NP; and E N 2 and E O 2 are the total energies of the N 2 and O 2 molecules in their electronic ground state, which for the O 2 molecule is a triplet state. This definition of reference state of element is consistent with previous studies. ,, Consequently, the nitrogen molecule is taken as a convenient reference, and from the energy balance in eqs and , we do not expect any difference when employing a different source of nitrogen. In fact, different nitrogen precursors are used in experimental studies such as ammonium hydroxide or ammonia.…”
Section: Computational Strategy and Titania Modelssupporting
confidence: 85%
See 2 more Smart Citations
“…The formation energy labeled as E f is defined as E normalf , N s = E normalN @ Ti 84 O 167 + 1 2 E normalO 2 1 2 E normalN 2 E Ti 84 O 168 E normalf , N i = E normalN @ Ti 84 O 168 1 2 E normalN 2 E Ti 84 O 168 where E N@Ti 84 O 167 and E N@Ti 84 O 168 correspond to the total energies of substitutional and interstitial doped NPs, respectively; E Ti 84 O 168 is the total energy of the undoped NP; and E N 2 and E O 2 are the total energies of the N 2 and O 2 molecules in their electronic ground state, which for the O 2 molecule is a triplet state. This definition of reference state of element is consistent with previous studies. ,, Consequently, the nitrogen molecule is taken as a convenient reference, and from the energy balance in eqs and , we do not expect any difference when employing a different source of nitrogen. In fact, different nitrogen precursors are used in experimental studies such as ammonium hydroxide or ammonia.…”
Section: Computational Strategy and Titania Modelssupporting
confidence: 85%
“…This definition of reference state of element is consistent with previous studies. 19,26,35 Consequently, the nitrogen molecule is taken as a convenient reference, and from the energy balance in eqs 1 and 2, we do not expect any difference when employing a different source of nitrogen. In fact, different nitrogen precursors are used in experimental studies such as ammonium hydroxide or ammonia.…”
Section: Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…To 101) Anatase TiO 2 Surfaces and discovered that N001 is the most stable doping arrangement, with the nitrogen atom on the (001) side of the interface. kakil et al (Kakil et al 2020) demonstrated that nitrogen doping in TiO 2 anatase is subsurface depth dependent in substitution and interstitial doped forms, and that nitrogen impurity locations are dependent on nanocrystal facet (Kakil et al 2021). They also investigated the formation of nitrogen impurity in TiO 2 nanoparticles and how the mid-gap state of TiO 2 nanocrystal is generated, as well as how the nitrogen impurity locations depend on facet of nanocrystal.…”
Section: Theoretical: Computational Methods (Dft)mentioning
confidence: 99%
“…To 101) Anatase TiO 2 Surfaces and discovered that N001 is the most stable doping arrangement, with the nitrogen atom on the (001) side of the interface. kakil et al (Kakil et al 2020) demonstrated that nitrogen doping in TiO 2 anatase is subsurface depth dependent in substitution and interstitial doped forms, and that nitrogen impurity locations are dependent on nanocrystal facet (Kakil et al 2021). They also investigated the formation of nitrogen impurity in TiO 2 nanoparticles and how the mid-gap state of TiO 2 nanocrystal is generated, as well as how the nitrogen impurity locations depend on facet of nanocrystal.…”
Section: Theoretical: Computational Methods (Dft)mentioning
confidence: 99%